Analisis Kelayakan Finansial dan Prospek Pertumbuhan Usaha Pengolahan Rumput Laut di Desa Jang - Indah Asmarawati, Citra; Hidayat, Fizy (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
Jang Village, located in Moro District, Karimun Regency, has abundant seaweed resources utilized for various products, including collagen drinks. This study aims to analyze the financial feasibility of seaweed processing using parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Break Even Point (BEP). The analysis results indicate that the BEP is 1.236 units, with a BEP in Rupiah of Rp6.946,00, an NPV of Rp195.869.079,29, an IRR of 21%, and a PP of 4.4 months. Based on the evaluation of financial and non-financial aspects, the seaweed processing business run by CV. Moro's Pure Marine Collagen is considered feasible and profitable. The findings of this study are used to develop long-term business strategies, including global market expansion supported by digital marketing and product diversification such as sports supplements and skincare products. Competitive advantage is enhanced through product certification and continuous research. Business sustainability is achieved by implementing environmentally friendly practices and empowering coastal communities, which is expected to support local economic growth and maintain the sustainability of natural resources.